Pengaruh Pendidikan Ekonomi Keluarga, Literasi Keuangan dan Intensitas Penggunaan Media Sosial Terhadap Pengelolaan Dana Beasiswa Bidikmisi Mahasiswa Fakultas Ekonomi Universitas Negeri Malang Angkatan 2017 - Alexandria Nechita Sousa Pereira; Syahrul Munir (Jurnal Pendidikan Ekonomi, 2022)
The purpose of this research to knowÂ  the influence of family economics education, financial literacy and intensity of social media used on the management of bidikmisi scholarship fund for students at faculty of economics in Universitas Negeri Malang, Class of 2017. This study used a quantitative research approach with the type of explanatory research. The sample used 137 respondents of students recipients of the bidikmisi scholarship at the Faculty of economics, Universitas Negeri Malang class of 2017. Data collection techniques using a questionaire. Data analysis technique used classical assumption test, multiple linier analysis and hypothesis testing (F test and T test) with SPSS 24 For windows. Based on the analysis, the following results are obtained : 1) family economic education effects the management of bidikmisi scholarship funds for students of the faculty of economic Universitas Negeri Malang.; 2) Financial literacy effect the management of bidikmisi scholarship funds for students of the faculty of economic Universitas Negeri Malang; 3) Intensity of social media used effect the management of bidikmisi scholarship funds for students of the faculty of economic Universitas Negeri Malang; 4) family economic education, financial literacy and the intensity of the uses of social media simultaneously effect the management of the bidikmisi scholarship funds for students economics faculty Universitas Negeri Malang, class of 2017.DOI: https://dx.doi.org/10.17977/UM014v15i22022p125Â Â